IMPLEMENTING ONLINE CUSTOMER RELATIONSHIP MANAGEMENT IN SMALL AND MEDIUM SIZE ENTERPRISE (SME): CASES BALI HANDICRAFT SMALL INDUSTRY - Soetam Rizky Wicaksono (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2011)
Online customer relationship management (CRM) implementation is becoming such terrifying activity for most firms, especially those which are categorized as SME (Small and Medium size Enterprise). Since that SME often lack of technical expertise and they really care for cost spending especially in internet connection cost. However, those barriers actually can be released when its implementation is being done with proper technology that can reduce cost while it will not reduce customer satisfaction in using online CRM. This paper tries to explain online CRM implementation in SME that will break all worries of SME’s management. On the other hand, brief literature review can bring clear explanation for importance of online CRM implementation in many level of industry.